Holistic Learning: Integrating Knowledge for Lifelong Benefit Through Natural Human Learning Processes - Rasri, Warit; Promduea, Somsak; Bamrungchai, Somchao; Kanyarat, Man (Journal of Education and Learning Reviews, 2024)
Background and Aims: Integrating knowledge through natural human learning processes promotes lifelong learning because it aligns education with how people naturally acquire and apply knowledge. This approach promotes adaptability and personal growth, ensuring that learning is relevant and applicable throughout life. This paper aims to explore Integrating Knowledge for Lifelong Benefit Through Natural Human Learning Processes. Methodology: The methodology for this paper is a systematic review of academic databases and theoretical texts. The analysis combines common themes, theoretical frameworks, and empirical evidence to compare holistic and traditional learning models, emphasizing the lifelong benefits of holistic education. Results: The finding found that the study of holistic learning reveals that it combines cognitive, emotional, and practical dimensions, providing learners with critical thinking, emotional intelligence, and real-world problem-solving abilities. Successful programs, such as Montessori and Reggio Emilia, demonstrate the effective application of these principles, fostering holistic development. Conclusion: The study of holistic learning demonstrates that it incorporates cognitive, emotional, and practical dimensions, providing learners with critical life skills. Montessori and Reggio Emilia programs are prime examples of how these principles can be successfully applied to promote well-rounded development.